Analisis Keterampilan Dasar Mengajar Guru dalam Melaksanakan Proses Pembelajaran Ilmu Pendidikan Alam - Ripka Aspia Siregar (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas Gunung Tua, 2024)
The importance of applying basic teaching skills for teachers in the learning process is crucial. In this context, there is a need to evaluate and understand the basic teaching skills implemented by the homeroom teachers of classes IV-A and IV-B. Through this research, it is hoped that the factors influencing teachers' teaching skills and their impact on the quality of learning can be identified. The research method used is a qualitative approach with observation and interview techniques. The researcher conducted direct observations of the learning process in class IV to assess the basic teaching skills of the teachers, as well as interviews with both teachers and students to gain deeper perspectives. The data collected was analyzed descriptively. The results of this research are described based on two aspects: the basic teaching skills applied by the teachers in delivering science lessons in class IV of SDN 101630 Portibi, which include the skills of opening and closing lessons, explaining lessons, questioning in lessons, providing reinforcement, giving variety, managing the classroom, leading groups, and leading small group discussions. The factors influencing the basic teaching skills of class IV teachers at SDN 101630 are divided into two categories: internal factors and external factors.